The Workload Pressures Experienced by Nurses at Public Sector Hospitals, Peshawar - Hassan Mehmood Khan; Wajiha Qamar; Mehran Qayum; Naveed Sadiq; Nadia Pervaiz; Shifa Haider Sawal (Gandhara University, 2022)
OBJECTIVE The study's objective was to assess that nurses working in in-patient wards were under workload stress. METHODOLOGY Descriptive observational research on nurses working in the in-patient ward of a public sector hospital in Peshawar was undertaken in November 2020. Workload Indicators of Staffing Need (WISN), a tool established by the World Health Organization (WHO) to anticipate the number of health staff needed to cope with workload pressure, was used to determine nurses' workload. To ensure the successful implementation of the WISN methodology, three tiers of committees were developed, including steering, technical, and expert committees. Data were also analyzed using the tool. RESULTS Nurses in the hospital's in-patient unit work 1966 hours per year. Health service activities, support, and other activities account for 47.92%, 33.33%, and 18.75% of all nurses' time, respectively, during this time. Four nurses were working in the hospital during the research study; however, WISN estimated that three nurses were needed to cope with the ward's workload pressure, and one nurse was overstaffed at the time. The WISN ratio calculated was 1.33. CONCLUSIONS The study concluded that there was no workload pressure on nurses (negative), and the ward had an extra nurse who could be accommodated in any other department with greater demand.